2011
DOI: 10.1126/scitranslmed.3002356
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Dosing for EGFR-Mutant Non–Small Cell Lung Cancer with Evolutionary Cancer Modeling

Abstract: Non–small cell lung cancers (NSCLCs) that harbor mutations within the epidermal growth factor receptor (EGFR) gene are sensitive to the tyrosine kinase inhibitors (TKIs) gefitinib and erlotinib. Unfortunately, all patients treated with these drugs will acquire resistance, most commonly as a result of a secondary mutation within EGFR (T790M). Because both drugs were developed to target wild-type EGFR, we hypothesized that current dosing schedules were not optimized for mutant EGFR or to prevent resistance. To i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
472
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 474 publications
(503 citation statements)
references
References 59 publications
27
472
3
1
Order By: Relevance
“…For example, the metabolic region of EGFR1 tumors was smaller and had a lower SUV max than EGFR-tumors. Because of their low SUV uptake and smaller MTV, our results are consistent with the notion that EGFR mutants tend to be more indolent than other lung cancer types (39,40). In addition, 8 radiomic features were significantly associated with and predictive of EGFR mutation status, where InvDiffmomnor was the most predictive for EGFR mutation status and significantly outperformed the conventional measure MTV (P # 0.02).…”
Section: Discussionsupporting
confidence: 78%
“…For example, the metabolic region of EGFR1 tumors was smaller and had a lower SUV max than EGFR-tumors. Because of their low SUV uptake and smaller MTV, our results are consistent with the notion that EGFR mutants tend to be more indolent than other lung cancer types (39,40). In addition, 8 radiomic features were significantly associated with and predictive of EGFR mutation status, where InvDiffmomnor was the most predictive for EGFR mutation status and significantly outperformed the conventional measure MTV (P # 0.02).…”
Section: Discussionsupporting
confidence: 78%
“…The detection of the EGFR T790M mutation in this setting has become clinically necessary because of the development of third-generation EGFR TKIs, such as osimertinib, which are active in the presence of this mutation. 223,224 However, although rare responses have been reported to third-generation inhibitors in EGFR T790Menegative disease, 225 such cases may harbor other resistance mechanisms such as MET or ERBB2 amplification 90,114,226 that may be more effectively targeted by other agents. Therefore, determining appropriate therapy in the setting of secondary clinical resistance to an EGFR inhibitor requires knowledge of the presence or absence of the T790M mutation.…”
Section: Recommendationmentioning
confidence: 99%
“…Experimental studies have shown that the presence of an EGFR T790M mutation in small proportion of a bulk tumor cell population (as little as 5%), often undetectable by Sanger sequencing, can lead to increased growth in spite of treatment with EGFR TKI. 225,227 Detection is made even more challenging when biopsies contain a high proportion of nontumor cells. These considerations lead us to recommend that laboratories should have a high sensitivity assay available for the detection of the EGFR T790M mutation in posttreatment biopsies from patients who demonstrate progression or relapse after an initial response to EGFR TKI.…”
Section: Recommendationmentioning
confidence: 99%
“…This event has been previously shown to occur in other cancer types. Chmielecki and colleagues ( 78 ) demonstrated that erlotinib-resistant NSCLC cells grew more slowly than their sensitive counterparts, and, interestingly, resistance was not maintained in the absence of the drug. A similar phenomenon has been described for BRAF -mutant melanoma cells, which become resistant to vemurafenib through expression of EGFR ( 79 ).…”
Section: Reviewmentioning
confidence: 99%